2017
DOI: 10.1007/s00264-017-3438-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a non-randomised prospective cohort of one hundred and ninety two total knee arthroplasties using the NexGen implant

Abstract: This study showed optimal survivorship of the NexGen LPS, associated with a significant improvement in overall outcomes at a minimum follow-up of 15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…3 Implant-specific survivorship plot at follow-up of 16 years, demonstrating cases that were revised for an implant related cause. Three cases of instability and one non-specific pain rate than Lutzner et al [28] and Panni et al [34] but compatible with registry data [15,16]. Of the 10 revision surgeries, 50% of revision could conceivably be attributed to the implant itself including three patients revised for instability and 2 revised due to non-specific pain.…”
Section: Follow-up Time (Years)supporting
confidence: 80%
See 1 more Smart Citation
“…3 Implant-specific survivorship plot at follow-up of 16 years, demonstrating cases that were revised for an implant related cause. Three cases of instability and one non-specific pain rate than Lutzner et al [28] and Panni et al [34] but compatible with registry data [15,16]. Of the 10 revision surgeries, 50% of revision could conceivably be attributed to the implant itself including three patients revised for instability and 2 revised due to non-specific pain.…”
Section: Follow-up Time (Years)supporting
confidence: 80%
“…In fact, the mean index age at the time of TKA was 63 years and this seems to be an issue in several other reports [27][28][29]. To our knowledge there are few studies that have than 10 years of followup of NexGen Posterior Stabilized TKA system [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…Pooled analysis of data derived from case series reported at exactly 15 years or 20 years showed an all-cause construct survivorship of 96·3% (95% CI 95·7–96·9) at 15 years and 94·8% (92·5–97·1) at 20 years. Figure 2A shows a forest plot for the meta-analysis of data on TKRs derived from case series at 15 years and 20 years.
Figure 2Forest plot of estimates for reported survival of knee replacements from case series11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32(A) Total knee replacements at 15 years and 20 years. (B) Unicondylar knee replacements at 15 years, 20 years, and 25 years.
…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have reported that malalignment after TKA is not a determinant factor for the survival of prosthesis. 22 23) Therefore, the concept that the mechanical axis should correspond to a safety zone defined as within 3° of neutral limb alignment is being challenged. 24 25) Furthermore, some studies have suggested a change of paradigm in definitive, ideal coronal alignment and implant positioning for TKA.…”
Section: Discussionmentioning
confidence: 99%